Effect of Acquisition on Operating Performance of Indigenous Oil & Gas Firms in Nigeria (International Journal of Scientific Research and Management (IJSRM), 2018)
Growth through acquisition has been a critical part of the success of many companies operating in the new economy like that of Nigeria. It is an indisputable fact that acquiring is much faster than building, speed-speed to market, speed to positioning and speed to becoming a viable company is absolutely essential in the new economy. This study evaluated the effect of acquisition on the operating performance of two oil & gas firms in Nigeria. Five research objectives, questions and hypotheses were formulated and analyzed. The study made use of secondary data. The secondary data was gotten from the financial statement of studied firms’ and were used in testing the hypothesis. In testing the formulated hypotheses, variables such as Return on Equity, Return on Assets, Gross earnings, Asset Utilization, & Financial Leverage were compared before and after acquisition using Pair Sample T-Test Statistical Tool. All the results show that the preacquisition financial positions were better off than the post-era. The study identified some of the likely reasons that could account for post-era poor performance to include hostility in the Niger Delta region which has led to pipeline vandalism, drop in oil price etc. The study hereby recommend that Since the oil price cannot be predicted, both firms should diversify some of their operations in activities that are a bit stable, profitable and competitive. The government should ensure that the relative peace experienced so far is being maintained to avoid pipeline vandalism which has adverse effect on oil production.